The idea of the university in modern challenges - Dolska, Olga; Dyshkant, Tetiana (Право, 2023)
The article, exploring the genesis of the idea of the university, reveals how its value bases and mission have changed over time. The fate of the university as a social institution is inextricably linked with society and bears the imprint of the transformations taking place in the social environment. In relation to the university in the modern world, the existence of a serious crisis is universally stated and, as shown in the article, it is associated with the processes of globalization, the establishment of market fundamentalism and postmodern culture.

У статті, за допомогою розгляду генези ідеї університету, виявляється, як із часом змінювалися його ціннісні основи та місія. Доля університету як соціального інституту нерозривно пов’язана із суспільством і несе на собі відбитки трансформацій, що відбуваються в соціальному середовищі. Щодо університету в сучасному світі повсюдно констатується наявність серйозної кризи, і, як показано у статті, вона пов’язана з процесами глобалізації, утвердженням ринкового фундаменталізму та постмодерної культури.
Ідея університету в сучасних викликах
Keywords: university; university mission; crisis in education; university models; globalization; deglobalization; modernity crisis; університет; місія університету; криза в освіті; моделі університету; глобалізація; деглобалізація; криза сучасності